Ochrona praw kobiet w systemie Rady Europy - Wojnowska-Radzińska, Julia (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The legal system of the Council of Europe is of crucial importance for the protection of women’s rights and preventing discrimination based on sex. The European Convention on Human Rights constitutes one of the most efficient tools for establishing standards for the protection of women’s rights. Despite the fact that the Convention does not include detailed provisions on protection of women’s rights, it has been adopted and implemented in the spirit of equal rights for men and women and the prohibition of discrimination. The potential power of the Council of Europe in the area of protecting women’s rights is also evidenced by the jurisdiction of the European Court of Human Rights in Strasbourg, which supervises whether the provisions of European Convention on Human Rights are complied with or not. In case any state that is a party to the Convention breaches its provisions, women can lodge individual complaints with the Court, regardless of citizenship.